Optimized PAPR Reduction Approach by Partial Approximate Gradient Constellation Algorithm for Better Efficiency (International Journal of Engineering and Computer Science, 2018)
In the OFDM communication system, the main disadvantage factor is Peak Average to Power Ratio (PAPR) which limits the performance of the overall system. To limit this factor in the OFDM system there are so many techniques that depends on the nature of the system like clipping, Partial transmission, Selective mapping, Companding transform etc, In this paper, a combinational approach is proposed for peak-to-average power ratio reduction in orthogonal frequency division multiplexing . The key idea of the proposed scheme is to apply partial transmit sequence and approximate gradient project schemes .These two schemes are applied in parallel on two equal halves of subcarrier in an OFDM standard. On one half, partial transmit sequence minimizes the PAPR of OFDM symbols through disjoint sub blocks and optimized phase factor. Approximate gradient project extends the outer constellation points of OFDM symbols dynamically within margin-preserving constraints to reduce the peak magnitude of symbols model ,on the other half. The simulation results show that a reduced PAPR and optimal BER rate of the OFDM system. The data rate is improved and also the computational complexity is reduced when our proposed scheme is compared with the partial transmit sequence scheme